Repellent Effect of Indigenous Plant Bhat (Clerodendron Viscosum L.) Leaf on Tribolium Castaneum Herbst (Bangladesh Journal of Scientific and Industrial Research, 2007)
Repellent response of Bhat (Clerodendron viscosum L) to adult and larvae of Tribolium castaneum was studied. Results indicated that both the adults and larvae were repelled by contact with food medium treated with Bhat leaf dust conditioned with 100, 500, 1000 and 2000 ppm of flour. Bangladesh J. Sci. Ind. Res. 41(1-2), 67-72, 2006